The influences of age on lactation length and milk yield in Kenana and Butana cows - Abdalla, E.A.; Nasr, A.M.; Khalafallah, A.M.; El Shafie, S.A. (1990)
Milk yield performances in Kenana and Butana cows were examined to determine the influence of age on production. The mean milk yields for the Kenana and Butana herds were 2136 ± 168 and 1807 ± 592 kg produced in a mean lactation period of 283 ± 40 days and 283 ± 57 days respectively. In both herds the maximum lactation milk yield was attained in the third lactation. Kenana cows between 6½ - 7½ years of age and Butana cows between 5½ - 6½ years of age attained the maximum lactation milk yield.